Prevalence and Characterization of Food-Related Methicillin-Resistant Staphylococcus aureus (MRSA) in China - Wu, Shi; Huang, Jiahui; Zhang, Feng; Wu, Qingping; Zhang, Jumei; Pang, Rui; Zeng, Haiyan; Yang, Xiaojuan; Chen, Moutong; Wang, Juan; Dai, Jingsha; Xue, Liang; et al. (Frontiers in Microbiology, 2019)
Methicillin-resistant Staphylococcus aureus (MRSA) is an emerging pathogen that is difficult to treat due to the multiresistance of the bacteria upon infection. From 2011 to 2016, 1581 S. aureus strains were isolated from 4300 samples from retail foods covering most provincial capitals in China. To determine the prevalence of food-related MRSA and its genetic background in China, antibiotic resistance, staphylococcal toxin genes, staphylococcal cassette chromosome mec (SCCmec) typing, spa-typing and MLST were carried out in this study. In total, 108 (7.4%) isolates were confirmed for MRSA by phenotyping (cefoxitin) and genotyping (mecA/mecC gene). A total of 52.8% (57/108) of the MRSA isolates belonged to clonal complex 59 (CC59) (ST59, ST338 and ST3355), which was the predominant clone in this study. These CC59 isolates carried SCCmec elements of type IV, V or III and exhibited spa type t437, t441, t543, t163, t1785 or t3485, and half of them carried major virulence genes, such as the Panton-Valentine leucocidin gene. The secondary clones belonged to ST9 (15.7%, 17/108) with a type of t899-SCCmec III and showed a broader range of antimicrobial resistance. The remaining MRSA isolates (31.5%, 34/108) were distributed in 12 different STs and 18 different spa types. All isolates harboured at least one of the enterotoxin genes, whereas only 4 isolates (3.70%) were positive for the toxic shock syndrome toxin tsst alleles. For antibiotic susceptibility testing, all isolates were resistant to more than three antibiotics, and 79.6% of the isolates were resistant to more than 10 antibiotics. Amoxycillin/clavulanic acid, ampicillin, cefoxitin, penicillin, ceftazidime, kanamycin, streptomycin, clindamycin and telithromycin was the most common antibiotic resistance profile (55.6%, 60/108) in the study. In summary, this study implied that the major food-related MRSA isolate in China was closer to community-associated MRSA, and part of the remaining isolates (ST9-t899-SCCmec III) were supposed to livestock-associated MRSA. Besides, most MRSA isolates showed resistance to multiple drugs and harboured staphylococcal toxin genes. Thus, the pathogenic potential of these isolates cannot be ignored. In addition, further studies are needed to elucidate the transmission routes of MRSA in relation to retail foods and how to prevent the spread of MRSA.